Komiesa ko speel: Heteroglossia and Multimodality in bilingual children's play in a pre-school space - Daniels, Sharon (School of Education, 2024)
This study examines teachers' and parents' language ideologies which in turn influence the choices about languages they choose for socialising young emergent bi(multi)linguals and determining their identities. It also explores bi(multi)lingual children's heteroglossic practices and multimodal communication in their play in a pre-school setting and contrasts them with the teacher's language and literacy practices. The first part of this theoretical framework examines language ideologies such as monoglossia, monolingualism, Anglonormativity and raciolinguistic ideologies and how these position children as language learners. These ideologies are juxtaposed against the concept of heteroglossia to highlight how a paradigm shift offers a different way in which we could position children. The second part explores language and literacy as social practice from the NLS theoretical conceptualisation including, orality, multimodality and materiality and their relevance for children's language and literacy development and their personal development in general. It also draws on the sociocultural theory of Vygotsky with particular reference to playing and learning and concepts such as mediation, scaffolding, the Zone of Proximal Development (the ZPD) and self-regulation. The combination of these two strands of sociocultural theory enables one to understand the holistic development of children as the concepts encompass a greater spectrum of not only the children's sociocultural doings, communication and interaction with the environment but also how it affects how they are taught and how they learn. The research methodology encompassed working within language and literacy as a social practice and the research design for this study was implemented as an exploratory, descriptive, interpretive and qualitative case study that draws on linguistic ethnographic data collection and analytic tools. Thus, it is not a full ethnographic study but draws on the important tenets of ethnography. The research reveals that language ideologies of monoglossia, monolingualism, Anglonormativity and raciolinguistics are practised and propagated daily even though colonialism and apartheid have been seemingly abolished. Furthermore, it has shown that standardised languages are promoted and have a value attached to them as well as the belief that should people master said languages, their economic and social status would improve. One of the consequences of these ideologies is foregrounded through the conflict experienced by the participants as, due to the negative attitudes towards Kaaps, they do not want to be perceived as uncultured and uneducated. That teachers socialise the children to conform to school rules and are sometimes prescriptive in their pedagogy, which stifles their language development and communicative ability, has been illustrated in this study. It also shows how the children rebel against the stringent orderliness of the rigours of classroom practice when they are released to play is depicted. Moreover, the enormous value of play to children's holistic development highlights how it is irreplaceable for young children's development. The study challenges the view that some languages or vernaculars are superior to others and argue for opportunities to incorporate the concept of Heteroglossia to offer a different way in which we could position the children. Also, multilingualism should be embraced and normalised in communities and schools and not be relegated to demarcated spaces of usage. I also argue for a greater understanding of the children's language and literacy learning and how it is embedded in their daily socio-cultural ways to inform pedagogy from below. As children are accomplished at play, this activity should be encouraged, as opposed to it being restricted or used only as a reward. Furthermore, as play has been increasingly substituted by teacher-led academic instruction, it is important to research this aspect of pedagogy to try a find a balance. Lastly, this study highlights how important it is to listen to, observe and involve children in their development so that they are not overlooked and simply assimilated into the adult way of doing things.